Growth stage sensitivity of wheat to irrigation water salinity (Journal of the Bangladesh Agricultural University, 2014)
The effects of irrigation water salinity (12 dS m?1), imposed at maximum tillering (35?40 days after sowing, DAS) or booting (50?60 DAS) or grain filling (75?85 DAS) stage of wheat, on growth and yield of the crop was demonstrated. The experiment comprised four treatments I1: irrigation by fresh water (FW) at all three growth stages (control), I2: irrigation by saline water (SW) at maximum tillering stage and by FW at other stages, I3: irrigation by SW at booting stage and by FW at other stages, and I4: irrigation by SW at grain filling stage and by FW at other stages. The experiment was set in a randomized complete block with three replications. Wheat was grown under three irrigations (each of 3 cm) and recommended fertilizer doses (120 kg N, 32 kg P, 62 kg K, 20 kg S, 3 kg Zn and 1 kg B ha?1). Salinity of irrigation water imposed, separately, at the three growth stages did not impart significant (p = 0.05) negative influence on plant height, spike density, spike length, spikelets and grains per spike and 1000-grain weight. It, however, significantly hindered leaf area index (LAI), above ground dry matter (ADM), grain and straw yields, grain-straw ratio and water productivity of the crop. The least grain (3.622 t ha?1) and straw (5.772 t ha?1) yields, LAI (1.24 and 2.18 at 50 and 70 DAS, respectively), ADM (0.80, 4.78 and 7.66 t ha?1) and water productivity (186.5 and 297.3 kg ha?1 cm?1) obtained under I3 implied that salinity of irrigation water imposed at booting stage exerted the maximum retarding effects on the growth and yield of wheat. Grain yield decreased by 13.4% in I3 over the control, I1. An increase in grain and biomass yields by 14.3 and 11.9%, respectively under I2 over I1 demonstrated a positive contribution of irrigation water salinity imposed at maximum tillering stage of wheat. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18226 J. Bangladesh Agril. Univ. 11(1): 147-152, 2013